A preliminary study to investigate the serum urea: creatinine ratio in canine babesiosis in South Africa - Lobetti, R.G. (Remo Giuseppe) (University of Pretoria, 2013)
Dissertation (MMedVet (Medicine))--University of Pretoria, 2005.